Microgeographic spatial structuring of Triatoma infestans (Hemiptera: Reduviidae) populations using wing geometric morphometry in the Argentine Chaco - Gaspe, Maria Sol (2012)
We investigated the occurrence of spatial structuring in Triatoma infestans (Klug) (Hemiptera: Reduviidae) populations 12 yr after the last community-wide insecticide spraying campaign in rural Pampa del Indio, in the Gran Chaco of northeastern Argentina. In total, 172 male and 149 female right wings collected at 16 georeferenced sites with at least 10 individuals of the same sex were analyzed using geometric morphometry. Mean female body length and wing centroid size (CS) were significantly larger than for males. Log-transformed CS and length were significantly and positively correlated both for males and females. Males collected in domiciles had significantly smaller CS than those collected in peridomestic structures both closed (kitchens or storerooms) or open (chicken coops), in agreement with our previous results elsewhere in the dry Argentine Chaco. Female wing CS was not significantly different between ecotopes. Wing shape analyses showed the occurrence of significant geographic structuring in males and females combined and in males only. Male wings showed a strong association between Mahalanobis distance and geographic distance. In general, Mahalanobis distances were significantly different between collection sites located >4 km apart. For collection sites located <4 km apart, the greater the geographic distance the larger the difference in wing shape variables. Among females, only a partial correspondence between geographic groups and Mahalanobis distances was recorded. The strong spatial structuring found in T. infestans populations may be useful for the identification of putative reinfestation sources after vector control interventions.